Characterization of the complete mitochondrial genome of the king pigeon (Columba livia breed king). (June 2015) - Zhang, Rui-Hua; He, Wen-xiao; Xu, Tong
Abstract The king pigeon is a breed of pigeon developed over many years of selective breeding primarily as a utility breed. In the present work, we report the complete mitochondrial genome sequence of king pigeon for the first time. The total length of the mitogenome was 17, 221 bp with the base composition of 30.14% for A, 24.05% for T, 31.82% for C, and 13.99% for G and an A–T (54.22 %)-rich feature was detected. It harbored 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and one non-coding control region (D-loop region). The arrangement of all genes was identical to the typical mitochondrial genomes of pigeon. The complete mitochondrial genome sequence of king pigeon would serve as an important data set of the germplasm resources for further study.